Interpretative models, between illusions and suggestions (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
The representation of “distant spaces” is proposed here through a transverse report between distant worlds and cultures. The chosen models are identified starting from considerations related to the way in which “the observer” stands in relation to the object shown, both related to sphere of real world and fantastic one. Nevertheless, if it is the observation point that affects the vision, visualization and interpretation of universe, drawing and images are used to outline its “allegorical” interpretations. The current visual culture is realized in a time when the multiple possibilities offered by science and technology allow to devise, manipulate and reveal visions and images of the “real world”.